1994
DOI: 10.1007/bf00188323
|View full text |Cite
|
Sign up to set email alerts
|

Anterior decompression and fusion for cervical myeloradiculopathy secondary to ossification of the posterior ligament

Abstract: The authors reviewed 85 patients who had undergone anterior decompression and cervical fusion for myeloradiculopathy due to ossification of the posterior longitudinal ligament. There were 72 males and 13 females; the average follow up was for 8.3 years. Sixteen patients (group I) underwent one vertebra subtotal spondylectomy with fusion, 58 (group II) two vertebra subtotal spondylectomy, and 11 (group III) three vertebra subtotal spondylectomy. Neurological recovery was assessed on the grading system of the Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In this regard, we have clinically demonstrated that favourable motor function recovery is expected when the compressive lesion causes less than 35-48% compromise of the cervical spinal canal [4,5]. Based on electrophysiological studies [2,10], we considered that the "threshold" for motor recovery against external compression is approximately 50-60% of spinal canal compromise, although this may be rather empirical.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this regard, we have clinically demonstrated that favourable motor function recovery is expected when the compressive lesion causes less than 35-48% compromise of the cervical spinal canal [4,5]. Based on electrophysiological studies [2,10], we considered that the "threshold" for motor recovery against external compression is approximately 50-60% of spinal canal compromise, although this may be rather empirical.…”
Section: Discussionmentioning
confidence: 97%
“…These studies suggested that postoperative functional recovery apparently correlates with the degree of cord compression preoperatively [5,6,34]. Several studies have examined the prognostic value of radiological morphometry of the cord in neurosurgical treatment [4,5,15,47]. For example, autopsy findings of the cervical spinal cord subjected to long-term compression by an ossified posterior longitudinal ligament have shown that serious neuronal loss, particularly in the anterior horn, contributed to the profound motor paresis [15,20,25,34].…”
Section: Discussionmentioning
confidence: 97%
“…15 This is very important with respect to the biomechanics of the spine, because the site and extent of anterior decompression can have significant impact on spinal instability. 3 Three-point fixation and the small bone grafts that are used in OWC mean that there is lower risk of pseudoarthrosis and infection compared with conventional corpectomy with strut-graft placement. None of our 15 OWC patients developed problems with pseudoarthrosis, infection, chronic inflammation; screw loosening, screw avulsion, or plate breakage in long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical corpectomy, posterior cervical laminectomy, and laminoplasty have been the most popular techniques for many years. [1][2][3][4][5][6][7][8][9][10] In cases of cervical compressive myelopathy, the purpose of surgical intervention is to decompress the spinal cord and nerve roots, to maintain stability and alignment of the cervical spine. There is still debate over which surgical approach is most appropriate for this condition.…”
mentioning
confidence: 99%
“…Anterior cervical discectomy and interbody fusion has been supported in the literature as an effective treatment of cervical disc degenerative disorders, with advantages of this procedure including direct decompression of spinal cord and nerve roots, immediate stability of involved segments, restoration of cervical lordosis and intervertebral height [2,9]. The tricortical iliac autograft has often been used as bone graft in interbody fusion after anterior intervertebral decompression with high fusion rates, but it has often been reported to have donor site complications [5,19].…”
Section: Discussionmentioning
confidence: 99%